Die Entstehung komplexer Siedlungen im Zentraloman : Archäologische Untersuchungen zur Siedlungsgeschichte von Al-Khashbah - Schmidt, Conrad, -1932, (Arabia Orientalis. Studien zur Archäologie Ostarabiens ;, 2021)
This volume presents the results of a survey conducted in 2015 and beyond by the Institut für die Kulturen des Alten Orients of the Universität Tübingen in Al-Khashbah, one of the largest Early Bronze Age sites on the Omani Peninsula. Ten monumental buildings, 273 tombs and other structures from the Hafit (3100-2700 BC) and Umm an-Nar periods (2700-2000 BC) were documented here. This makes Al-Khashbah ideally suited for the investigation of the beginnings of complex settlements and social structures in northern Inner Oman at the transition from the 4th to the 3rd millennium BC, because many of the achievements previously attributed to the Umm an-Nar period, such as monumental architecture and the smelting of copper, can already be proven here in the preceding Hafit period. In the Umm an-Nar period, the development of Al-Khashbah continues steadily, giving the site additional importance.